Coronary Artery Anomalies: A Review of More than 10,000 Patients from The Clayton Cardiovascular Laboratories - Wilkins, Charles E. (1988)
We reviewed the records of 10,661 patients who had undergone coronary angiography at the Clayton Foundation Cardiovascular Laboratories between 1 June 1974 and 15 March 1986, and identified major coronary artery anomalies in 83 adults. In addition, we included in our review 9 adults and 2 adolescents who had been referred for evaluation of anomalies documented elsewhere. Here we present the clinical and angiographic data for all 94 patients (76 men and 18 women). Most patients were men who presented with chest pain. The most common anomaly, found in 38 patients, was origin of left circumflex coronary artery from right coronary artery or right aortic sinus. In contrast to other studies, which have not shown increased incidence of coronary atherosclerosis in the anomalous circumflex artery, 71% of our patients with this anomaly had significant coronary atherosclerosis in the proximal portion of the anomalous vessel. The posterior course of the anomalous circumflex coronary artery may predispose this vessel to atherosclerosis in patients with coronary disease. The overall incidence of atherosclerotic disease in coronary arteries was 68% (64 of 94 patients) in the present study. (Texas Heart Institute Journal 1988;15:166-173)